Utilizing Q methodology to explore university students’ perceptions of the organic food industry: the integral role of social media - Nayak, Swayangsiddha; Campbell, Julie; Duffey, Kate Cassity (Frontiers in Communication, 2024)
The ascendancy of social media as a predominant source of information has underscored the imperative to grasp its impact on individuals' perceptions and behaviors across diverse industries.In the realm of organic farming, which often sparks conflicting perspectives among stakeholders, the inundation of user-generated content presents a formidable challenge in discerning reliable sources from dubious ones. This phenomenon risks perpetuating misinformation, particularly among younger consumers, with uncertain implications for Agricultural Education and Communication. To address this void in understanding how social media influences perceptions of organic farming, a study was undertaken at the University of Georgia, utilizing Q methodology to delve into the perspectives of undergraduate and graduate students regarding organic food and farming practices. Complementing this approach, an offline survey questionnaire assessed their purchasing habits and media consumption patterns. Through the sorting of 41 statements encompassing themes such as health, socioeconomics, environment, ideological beliefs, and ethics, the study identified four distinct consumer typologies: "Dilettante Consumers," "Decisive Consumers," "Need-based Consumers," and "Wandering Consumers."Social media platforms such as Instagram and YouTube were identified as the primary information sources for young consumers seeking information about the organic farming industry. Source attractiveness and perceived trustworthiness were identified as major attributes contributing to the credibility of social media as an information source among these consumers.However, their reliance on source expertise remained debatable. Notably, the research also unveiled that students' experiential learning facilitated a more nuanced understanding of various facets of the organic food industry. These findings emphasize the necessity for stakeholders to adapt to the digital age and remodel their communication strategies to better comprehend